2014
DOI: 10.1111/neup.12180
|View full text |Cite
|
Sign up to set email alerts
|

Short‐, middle‐ and long‐term safety of superparamagnetic iron oxide‐labeled allogeneic bone marrow stromal cell transplantation in rat model of lacunar infarction

Abstract: Recently, both basic and clinical studies demonstrated that bone marrow stromal cell (BMSC) transplantation therapy can promote functional recovery of patients with CNS disorders. A non-invasive method for cell tracking using MRI and superparamagnetic iron oxide (SPIO)-based labeling agents has been applied to elucidate the behavior of transplanted cells. However, the long-term safety of SPIO-labeled BMSCs still remains unclear. The aim of this study was to investigate the short-, middle- and long-term safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Cell labeling with SPIO was employed to track donor cells in the host brain by means of MRI. Cultured hBMSCs can uptake SPIO nanoparticles into their cytoplasm when the particles are added to the culture medium [7]. In the present study, Turnbull's Blue staining analysis showed that 34% hBMSCs in a chamber slide contained SPIO nanoparticles.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Cell labeling with SPIO was employed to track donor cells in the host brain by means of MRI. Cultured hBMSCs can uptake SPIO nanoparticles into their cytoplasm when the particles are added to the culture medium [7]. In the present study, Turnbull's Blue staining analysis showed that 34% hBMSCs in a chamber slide contained SPIO nanoparticles.…”
Section: Discussionmentioning
confidence: 47%
“…In the present study, Turnbull's Blue staining analysis showed that 34% hBMSCs in a chamber slide contained SPIO nanoparticles. Because SPIO nanoparticles have clearly detectable signal extinctions, SPIO-labeled cells were easily tracked anatomically with QSM MR images [7]. Histological analysis gained the same hBMSC distribution compared with MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these models also affect the whole brain (including the gray matter), and the lesions mimic more chronic leukoaraiosis rather than sudden onset focal ischemic white matter infarction (Wakita et al 1994, Kaiser et al 2014. Selective white matter lesions can be induced by stereotactic injection of ouabain, a Na/K ATPase pump inhibitor, as previously reported (Janowski et al 2008, Shichinohe et al 2013, Tan et al 2015). Ouabain's mechanism of injury is different from that of ischemia, but because the lesion mimics stroke according to MR imaging evaluation, this model may become an equivalent to the ET-1 method of white matter injury (Veldhuis et al 2003).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, our group developed a reproducible, reliable, and efficient method of ischemia-like injury in the deep-brain structures of rodents that closely mimics the lacunar stroke [6]. In the last few years, this model has been successfully used by other groups to study the safety and functionality of MSC transplantation [7, 8]. …”
Section: Introductionmentioning
confidence: 99%